THE CORRELATION STUDY BETWEEN LEARNING STYLE AND LEARNING OUTCOME OF THE FIRST-YEAR STUDENTS IN STRUCTURE ANALYSIS CLASS AT STUDY PROGRAM OF ENGLISH - SASI, DIYAH APRITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Learning Style, VAK Learning Style Model, VAK Learning Style SelfAssessment QuestionnaireLanguage is one of communication device which is used to deliver feeling message, or opinion within society. In learning language, many people are not aware of their own way in learning. Whereas, knowing the style of learning is useful which also influences the learning outcome. Therefore, this study is conducted to investigate learning style used by the students and its correlation on the students’ learning outcome. There are two objectives in this study, (1) to find out the learning style used by the first-year students at Study Program of English, and (2) to observe the correlation between learning style and learning outcome of the first-year students at Study Program of English. The writer also states two hypotheses, namely: (1) visual, auditory and kinesthetic learning style are found and used by the students of Study Program of English in structure analysis class, and (2) there is a correlation between learning style and learning outcome in the first-year students of Study Program of English.This study uses quantitative approach because the data are in form of number. It is also a correlation study since it tries to find out the correlation between learning style and learning outcome. The writer applies VAK model that divides learning style into visual (V), auditory (A) and kinesthetic (K). VAK Learning Style Self-Assessment Questionnaire is used as the instrument. It is regarded as the most appropriate questionnaire since the writer uses VAK model to find out the students’ learning style.The result shows that the students of English Study Program in structure analysis class use three types of learning style. The first type is auditory which is mostly used by the students and it is followed by kinesthetic and visual. Moreover, the writer also finds that the students’ learning style influences the final test score. It can be concluded that there is a correlation between learning style on learning outcome. Based on the finding, the first and second hypotheses are accepted.To complete this study, the writer suggests the next researcher to use the different theory, participants and other parameters such as age, gender or personality. The writer also suggests the readers and the students to find out their learning style surely. Besides, the writer suggests the lecturer to give suitable treatment based on the students’ learning style.